Blood beast - Shan, Darren (New York : Little, Brown, 2007)
When he begins experiencing alarming symptoms at the onset of the full moon, Grubbs Grady, who has so far escaped his family curse, fears that he is turning into a werewolf.
Keywords: Demonology -- Fiction; Werewolves -- Fiction; Horror stories